Space and Food in the City Cultivating Social Justice and Urban Governance through Urban Agriculture - Thornton, Alec (Springer International Publishing, 2018)
Urban social movements are influential agents in shaping cityscapes to reflect values and needs of communities. Alongside urban population growth, various forms of urban agriculture activity, such as community and market gardens, are expanding, globally. This book explores citizens' 'rights to city' and alternative views on urban space and the growing importance of urban food systems.